Advantages of endoscopic therapy of gastrojejunal dissociation in critical care patients - Shang, Edward; Kähler, Georg; Meier-Hellmann, Andreas; Scheele, Johannes (Intensive care medicine, 1999)
Objective: To evaluate the advantages of a new three-lumen tube (Trelumina) and a percutaneous endoscopic gastrostomy (EntriStar) with a jejunal insertion tube (PEGJ) as a safe method of early enteral nutrition and simultaneous gastric decompression as well as fast reduction of the high gastric reflux in critical care patients. Design: Retrospective, descriptive case series. Setting: Two anaesthesiological and one surgical intensive care unit (ICU) in a university hospital. Patients: Sixty-five consecutive critically ill patients with gastrojejunal dissociation. The mean Acute Physiology and Chronic Health Evaluation Score (APACHE II) was 19. Interventions: Placement of 46 Trelumina and 19 PEGJ under endoscopic control. Measurements and main results: None of the known percutaneous endoscopic gastrostomy (PEG) complications like wound infection, bleeding or organ perforation were seen. One secondary dislocation of the jejunal insertion tube and four dislocations of the jejunal part of the Trelumina were found. The average gastric reflux of the Trelumina and the PEGJ amounted to 1700 ± 230 ml/day. Forty-three patients showed a clear decrease in the gastric reflux to 450 ± 200 ml/day within the first 24 h of tube placement. The average time of reduction to normal gastric reflux volumes (0-200 ml/day) amounted to 4 ± 2 days. Forty-three (71 %) of the patients showed improved intestinal passage as expressed by regular peristalsis and defaecation. The price for 1 day enteral feeding via Trelumina or PEGJ was 10 times lower than 1 day total parenteral nutrition. Conclusions: Placement of the Trelumina and the PEGJ is a safe, successful and inexpensive means of early enteral nutrition and simultaneous gastric reflux reduction in critical care patients.